The Extraordinary Case of a Woman with a 30-Year-Long Diffuse Leishmaniasis Cured with One Single Ampoule of Intranasal Pentavalent Antimoniate - Sheila V. C. B. Gonçalves; Dorcas L. Costa; João da J. Cantinho-Junior; José N. Vieira-Junior; Edna A. Y. Ishikawa; Rubens N. Costa; Antônio C. G. Costa-Filho; Ronald da C. Araújo; Silvia R. B. Uliana; Jenicer K. U. Y. Yasunaka; Adriano C. Coelho; Jackson M. L. Costa; et al. (Pathogens, 2023)
Infection with Leishmania amazonensis and L. mexicana may lead to diffuse cutaneous leishmaniasis. The cure is exceptional, especially for the strange case of this lady. Case report: The patient acquired the disease in childhood and remained with lesions for over 30 years, albeit several treatments. She worsened after a pregnancy, developing disseminated lesions. Miltefosine with amphotericin B and pentamidine resulted in remission. Lesions reappeared after one year, accompanied by intra-nasal infiltration of the disease. The nasal spraying of a single ampoule of pentavalent antimoniate resulted in the sustained disappearance of the nasal symptoms and all the cutaneous lesions. After over eight years, she remains disease-free, albeit under renal replacement therapy. The high nasal mucosal antimonial concentration may explain the long-lasting cure via new MHC class I epitope-specific CD8+ cell clones against L. amazonensis present in the nasal mucosa.